Observations of wing-feather moult and summer feeding ecology of Steller's Eiders at Nelson Lagoon, Alaska - Petersen, Margaret R (Wildfowl, 1980)
The population size, moult chronology, food habits, and feeding behaviour of Steller's Eiders Polysticta stelleri were studied at Nelson Lagoon, Alaska from May to October 1977. Sub-adults were flightless from late July to late August and the adult males were flightless from late August to mid September. Adult females were rarely flightless at Nelson Lagoon but commonly flightless at Izembek Bay. Steller's Eiders ate primarily bivalve mollusca and amphipod crustacea, with Mytilus edulis and Anisogammarus pugettensis the most important foods. Eiders took amphipoda prior to the wing-feather moult, bivalves during the wing-feather moult, and both types of invertebrates after the wing-feather moult. Steller's Eiders fed primarily at the low tide by diving (flock-feeding) or head-dipping, both during the day and at night. There was no difference in feeding behaviour between ages or sexes. Eiders fed almost exclusively by diving after the wing-feather moult and apparently fed more as the season progressed.